The diagnostic value of serum Neuroapoptosis-regulating invertase (NARC1), von Willebrand factor (vWF), and ‌Protein G3a levels in type 2 diabetes patients with macrovascular lesions: Serum NARC1, vWF, and G3a levels in T2DM with macrovascular lesions - Wang, Yangyang; Jia, Suilin; Cai, Haolin; Zhang, Yige; Lv, Shuangyan (Journal of Medical Biochemistry, 2026)
[Objective] To evaluate the diagnostic value of serum Neuroapoptosis-regulating invertase (NARC1), von Willebrand factor (vWF), and ‌Protein G3a levels in type 2 diabetes patients complicated with macrovascular lesions. [Methods] The type 2 diabetes group consisted of 420 patients with the disease who were admitted to the hospital between January 2021 and June 2024. 150 healthy people who visited this hospital for checkups within the same time frame were chosen to be part of the healthy control group. Based on the diagnostic criteria for macrovascular disease, individuals with type 2 diabetes were split into two groups: 236 patients with simple diabetes and 184 patients with macrovascular disease. The changes in the serum NARC1, vWF and ‌Protein G3a levels in each group were observed, serum NARC1, vWF, and ‌Protein G3a levels in individuals with type 2 diabetes were compared before and after treatment using univariate, and the diagnostic efficacy of the three indicators in macrovascular disease complicated with type 2 diabetes was analyzed. [Results] Serum NARC1 and vWF levels were significantly greater in the type 2 diabetes group, although serum ‌Protein G3a levels were significantly lower (P<0.05) than in the healthy control group. Prior to therapy, the macrovascular lesion group’s serum NARC1 and vWF levels were considerably higher than those of the simple diabetes group (P<0.05). After treatment, the levels of serum NARC1 and vWF in both groups were significantly lower than those before treatment. However, the levels in the macrovascular lesion group were still greater than those in the simple diabetes group, and the difference was statistically significant (P<0.05). Prior to therapy, the macrovascular lesion group’s serum ‌Protein G3a level was considerably lower than the simple diabetes group’s (P<0.05). Although the difference was statistically significant (P<0.05), the group with macrovascular lesions still had a lower level than the group with simple diabetes. According to univariate analysis, the proportions of people aged ≥60 and with a diabetes course of ≥10 years, as well as low-density lipoprotein cholesterol and triglyceride levels, were considerably greater in the group with macrovascular lesions than in the group with uncomplicated diabetes, and the differences were statistically significant (P<0.05). Multivariate analysis revealed that patients with type 2 diabetes mellitus, increased levels of NARC1 and vWF were independent risk factors for macrovascular disease (P<0.05), whereas elevated serum ‌Protein G3a levels were a protective factor for macrovascular disease in type 2 diabetes mellitus patients (P<0.05). The sensitivity of the combined detection of serum NARC1, vWF and ‌Protein G3a in diagnosing type 2 diabetes complicated with macrovascular lesions was 89.4%, the specificity was 90.0%, and the area under the curve (AUC) was 0.959. The AUC was significantly greater than those of NARC1 (Z=4.160, P<0.01) and vWF (Z=4.059, P<0.01). Although individual ‌Protein G3a indications were found (Z=5.186, P<0.01). [Conclusion] NARC1, vWF and ‌Protein G3a are involved in macrovascular disease complicated with type 2 diabetes. When these three indications are detected together, they are highly effective in detecting macrovascular disease that is complicated by type 2 diabetes.